Optimization of the Application of Inclusive Teaching Style in Improving Learning Outcomes Forehand Push Table Tennis Game in Class XI IPA 1 Private Senior Highschool PAB Saentis - Winata, Devi Catur; Abadi, Andy Nur; Azandi, Filli; Fahmi, Mhd; Harahap, Bahder Johan (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
This study aims to find out how to improve learning outcomes of Forehand Push table tennis game through inclusive teaching style in class XI IPA 1 Private Senior Highschool PAB SAENTIS. The object of this research is class XI students with 25 students who will be given action in the form of inclusive teaching style on Forehand Push learning outcomes. In the first cycle, it could be seen that the students' initial ability to perform the Forehand Push technique was still low. Of the 25 students there are 15 people (60%) who have achieved mastery learning, while 10 people (40%) have not achieved mastery learning. With the average value of student learning outcomes is 76.3. Meanwhile, in the second cycle, it can be seen that the students' ability to perform classical learning outcomes tests has increased. Of the 25 students there are 20 (80%) who have achieved mastery learning, while 5 people (20%) have not achieved mastery learning. With the average value of student learning outcomes is 80.7, so there is a 25% increase in learning outcomes from cycle I to cycle II. It can be concluded that learning through inclusive teaching style can improve forehand push learning outcomes in class XI IPA 1 Private Senior Highschool PAB SAENTIS.